Diagnosis and Management of Persistent Trapezoid Dislocation Following Surgical Treatment of Second through Fifth Carpometacarpal Fracture Dislocation - Michael Flood, MD; Gregory Iovanel, MD; Muntazim Mukit, MD; Michael R. DiBenedetto, MD (Journal of Hand Surgery Global Online)
This case report highlights a persistent palmar trapezoid dislocation requiring return to the operating room following closed reduction and percutaneous pinning of second through fifth carpometacarpal joint fracture dislocations in the setting of ipsilateral distal radius fracture and distal radioulnar joint injury. The dislocation was identified on postoperative computed tomography imaging and required open reduction via dorsal approach. We offer this report to improve recognition of this rare presentation and to emphasize the importance of careful evaluation of intraoperative and postoperative imaging.